Pemanfatan Game Sebagai Media Belajar Pengenalan Ragam Rumah Adat Di Indonesia Berbasis Android: Indonesia - Muhammad Iqbal Rizmaya; Ade Bastian; Tri Ferga Prasetyo (J-ENSITEC (Journal of Engineering and Sustainable Technology), 2023)
Technological developments that continue to move very quickly, giving birth to various kinds of innovations that can be useful for life. Game is one of the products of computer technology, games that are in great demand and use, such as entertainment, learning media, promotional media and many more. has 34 provinces with a variety of customs and culture in each province. Every province in Indonesia has traditional houses which have their own uniqueness, and therefore it is very unfortunate if Indonesian citizens, especially children, do not know about them. Therefore there must be media that can reach both adults and children in introducing Indonesian customs and culture, especially traditional houses. Therefore a game was made "Educational Game for Various Indonesian Traditional Houses", which aims to be a learning medium by using technology and can also attract children's interest in traditional houses.